Declining democracy: autocratization in Indonesia during the Jokowi years - Taufik Taufik; Muhamad M.N Nadzri; Jamaie Hj. Hamil (Otoritas : Jurnal Ilmu Pemerintahan, 2023)
This article explores the decline of democracy in contemporary Indonesia during the Jokowi years. Jokowi's lukewarm commitment to democratic norms and illiberal attitude in running the government have made him an essentially conditional democrat, who is heavily influenced by the old political elite within a transitional political framework. As the result, Indonesia under the Jokowi's administration is entrapped with the old political practices, particularly oligarchic rules and political manipulation which awaken a new autocratization episode in its contemporary political history. This article is based on  interviews with eight key informants and supported with numerous secondary data from various sources. The article highlights three important points: first, the decline of democracy was caused by the old oligarchic, and cartelism practices. Second, Jokowi's superficial commitment to democracy essentially makes him a conditional democrat, rather than a progressive liberal. Third, Jokowi's leadership led to a new style of autocratization and authoritarianism in Indonesia which was influenced by the manoeuvring of the old political elite.